Formulation Options for Mucoadhesive Dosage Forms for Use in the Oral Cavity - Šimunková V.; Tichý E.; Špaglová M.; Potúčková M. (Sciendo, 2023)
Mucoadhesive dosage forms, which are used for topical application in the oral cavity, are currently a very intensively developing field in pharmaceutical technology. Considering the physiological conditions of the oral cavity, the formulation of these mucoadhesive forms is still a challenge. Various types and forms of polymers are used in the experiments, in combination with a large number of drugs, while the achieved effect can be local or systemic and the release rate can be controlled. For many drugs, buccal application is one of the ways to increase their bioavailability.